Urban and Rural Disparities in Women’s Reproductive Health Knowledge and Contraceptive use in Indonesia: A Cross-Sectional Study - Heny Nurma Yunita; Yuni Asri; Amin Zakaria; Muhammad Solihuddin Muhtar; Thomas Senghore (Jurnal Keperawatan Soedirman, 2026)
Reproductive health knowledge is essential for enabling women to make informed family planning decisions and prevent unintended pregnancies. In Indonesia, awareness of the possibility of pregnancy after childbirth before menstruation resumes remains insufficiently explored. This study examined sociodemographic, economic, and behavioral factors associated with women’s knowledge of postpartum pregnancy risk using data from 40,978 women aged 15–49 years in the 2017 Indonesian Demographic and Health Survey (IDHS). A cross-sectional analysis was conducted using multivariate logistic regression with sampling weights to ensure national representativeness. The results showed that higher education (AOR: 1.41; 95% CI: 1.13–1.75) and higher wealth status (AOR: 1.35; 95% CI: 1.21–1.50) were positively associated with knowledge. In contrast, rural residence (AOR: 0.91; 95% CI: 0.83–0.98) and lack of formal education were linked to lower awareness. Older age and being currently married were also associated with higher knowledge levels. Women using contraceptive methods, particularly calendar-based methods (AOR: 1.27; 95% CI: 1.15–1.40), were more likely to have adequate knowledge. These findings highlight urban–rural disparities in reproductive health knowledge and emphasize the need to strengthen education, expand healthcare access, and improve family planning counseling, particularly in underserved communities.